The anatomy of the brain - learned over the centuries - Bem, Luiz Severo; Lemos, Nilson Batista; De Lima, Luís Felipe Gonçalves; Dias, Artêmio José Araruna; Da Cunha Ferreira Neto, Otávio; De Lira, Carlos Cezar Sousa; Diniz, Andrey Maia Silva; Rabelo, Nicollas Nunes [UNESP]; Barroso, Luciana Karla Viana; Valença, Marcelo Moraes; De Azevedo Filho, Hildo Rocha Cirne (Scientific Scholar, 2021)
This article reports the evolution and consolidation of the knowledge of neuroanatomy through the analysis of its history. Thus, we propose to describe in a historical review to summarize the main theories and concepts that emerged throughout brain anatomy history and understand how the socio-historical context can reflect on the nature of scientific knowledge. Therefore, among the diverse scientists, anatomists, doctors, and philosophers who were part of this history, there was a strong influence of the studies of Claudius Galen (AD 129-210), Leonardo da Vinci (1452- 1519), Andreas Vesalius (1514-1564), Franciscus Sylvius (1614-1672), Luigi Rolando (1773-1831), Pierre Paul Broca (1824-1880), Carl Wernicke (1848-1905), Korbinian Brodmann (1868-1918), Wilder Penfield (1891-1976), Mahmut Gazi Yasargil (1925), and Albert Loren Rhoton Jr. (1932-2016) on the fundamentals of neuroanatomy.
Keywords: Anatomy; Brain; History of medicine; Neuroanatomy; Neurosurgery